CASE PHENOMENA IN THE ANNOUNCEMENT OF THE NEWS PROGRAM - F. S. Ragimova (Вестник Кемеровского государственного университета, 2015)
This article analyzes the news announcement, where the compression is formed by the use of certain linguistic resources, among which precedent phenomena play a significant role. One of the most important issues in the organization of media text is its scope, which is, on the one hand, is due to the rapid-growing volume of information flows, and, on the other, to the effort-saving tendency of the common language. Society demands a high text quality from the modern media. Any journalistic material is created in order to achieve particular results. To achieve the set goal, a journalist has to use particular means. The effectiveness of a media text, its language credibility and psychological suitability are essential parts of this technology, which is based on communication and mechanisms of influence on the recipient. The role of media in society is changing, informational and design technology develop, professional requirements to the authors of media texts are getting more complicated. All these tendencies demonstrate the need for special creative and applied approaches in both the creation of the text media and in its perception and processing. Precedent phenomena, included in the structure of the media text, serve this purpose.